2012
DOI: 10.1016/j.jval.2012.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Using a Molecular Diagnostic Test to Improve Preoperative Diagnosis of Thyroid Cancer

Abstract: Assuming 95% sensitivity and specificity of the Dx test when used as an adjunct to FNAB, the utilization of the DX test resulted in a gain of 0.046 quality-adjusted life-years (95% confidence interval 0.019-0.078) and a saving of $1087 (95% confidence interval $691-$1533) in direct costs per patient. If the cost of the Dx test is less than $1087 per test, we expect to save quality-adjusted life-years and reduce costs when it is utilized. Sensitivity of the DX test, compared with specificity, had a larger influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Patients with a false-negative result (ie, malignant pathology falsely diagnosed as benign) would therefore be at risk of delayed diagnosis and treatment. These patients may be at increased risk of recurrence and cancer-specific mortality (12,13). Patients with a positive test proceed with the standard management, that is, diagnostic thyroid lobectomy, followed by completion thyroidectomy if malignant.…”
Section: Designmentioning
confidence: 99%
“…Patients with a false-negative result (ie, malignant pathology falsely diagnosed as benign) would therefore be at risk of delayed diagnosis and treatment. These patients may be at increased risk of recurrence and cancer-specific mortality (12,13). Patients with a positive test proceed with the standard management, that is, diagnostic thyroid lobectomy, followed by completion thyroidectomy if malignant.…”
Section: Designmentioning
confidence: 99%
“…Attaining an accurate preoperative diagnosis of a thyroid nodule can prove difficult due to the lack of specific diagnostic tests for thyroid cancer. Consequently, 40-60% of thyroid surgery is performed for diagnostic purposes after non-diagnostic FNA cytology [[4]–[6]]. A specific molecular marker for thyroid cancer screening is desirable to avoid the resource burden of potentially avoidable surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cost analysis simulation examined the expected cost savings with the utilization of a diagnostic molecular marker for thyroid cancer in cases of indeterminate FNA cytology. Assuming a sensitivity and specificity of 95%, this study found that utilization of such a marker would result in a savings of $1087 in direct costs per patient as well as a significant gain in quality adjusted life years [[4]]. Costs to a publicly funded health care system were not addressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations